2018
DOI: 10.31832/smj.368978
|View full text |Cite
|
Sign up to set email alerts
|

Gıda Katkı Maddeleri

Abstract: DERLEME / Review Article ÖzetSonuç: Gıda katkı maddeleri ile sağlık üzerine yapılan bilimsel araştırmalar daha çok lezzet arttırıcı renklendiriciler ve koruyucular üzerine odaklanmıştır. Literatür taranarak bu konuda yapılan bilimsel araştırmalar derlenmiştir ( Sakarya Tıp Dergisi 2017, 7(4):164-167

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
3
1
1
Order By: Relevance
“…Similarly, in the study of Özmen et al, mothers whose children had an accident in the last year were found to have higher scores on the scale, and it was reported that they might have scored higher on the scale due to their experiences as a result of these accidents (5). Erdem et al In the study of Karatepe and Akis, the mean score was both higher and, unlike our study, the mean score was found to be higher in those who did not have a home accident (6,19). Similar to our study, Nadeeya and her friends (2016) state that mothers have moderate knowledge and perception scores regarding home injuries and safety precautions (31).…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Similarly, in the study of Özmen et al, mothers whose children had an accident in the last year were found to have higher scores on the scale, and it was reported that they might have scored higher on the scale due to their experiences as a result of these accidents (5). Erdem et al In the study of Karatepe and Akis, the mean score was both higher and, unlike our study, the mean score was found to be higher in those who did not have a home accident (6,19). Similar to our study, Nadeeya and her friends (2016) state that mothers have moderate knowledge and perception scores regarding home injuries and safety precautions (31).…”
Section: Discussioncontrasting
confidence: 84%
“…No significant relationship was found in terms of accident incidence according to mother's age, employment status, education level of mother or father, family type, housing type and economic status. Similarly, studies are showing that accident frequency is not affected despite the increase in maternal education (6,19,26). In some studies, the accident frequency of those whose mothers' education level was "university" was found to be higher than those whose mothers were in "primary school and below" (19,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu durum hem gıda endüstrisinde önemli ekonomik kayıplara hem de ciddi halk sağlığı sorunlarına neden olmaktadır (Tülüce ve ark., 2021). Bu kapsamda mikroorganizmaların gelişimini engelleyip bozulmayı yavaşlatmak ve raf ömrünü uzatmak için gıda katkı maddeleri olan antioksidanlar ve antimikrobiyal maddeler kullanılır (Atman, 2004;Karatepe & Ekerbiçer, 2017;Özkır, 2021).…”
Section: Introductionunclassified